ANALYSIS OF FACEBOOK USER PROFILING USING CLUSTERING IMPLEMENTATION - Noer Alam Yahya; Dhian Satria Yudha Kartika; Fauzan Atha (International Journal of Computer, Network Security and Information System, 2022)
In this era that is increasingly developing, it is possible that nearly some human beings use social media as a means of verbal exchange between users. It is not only a means of communique but using social media is used to show their own daily activities or habits. Social media is a media that functions as a medium for socializing from individual to individual based online using digital technology. Where the communication process is done via the internet. Of the several media used for socializing, Facebook is a very popular application. In the use of Facebook which can be accessed from all devices with the internet being the main role, there is a like feature provided by Facebook as a feature for socializing, of course there will be a comparison between the preferred data from some of these devices and from these data we can wonder why people chose mobile over computer or pc to access facebook. To calculate and analyze the existing data, we compared the data by conducting research and looking for Data Mining with the Clustering method using the K-Means Clustering algorithm.